Current situation and challenges of prevention and control of diabetes in China - NING Guang (Zhenduanxue lilun yu shijian, 2025)
Diabetes has become a major global public health issue. As of 2021， China had approximately 141 million diabetic patients， with 2/3 remaining undiagnosed， making China the country with the highest number of diabetes globally. This current status poses severe challenges to the prevention and control of diabetes and its complications. To effectively address these challenges， strategies must be comprehensive and involve multi-sectoral collaboration， including nationwide primary prevention， primary prevention for high-risk groups， and secondary prevention for diabetic patients. For the general population， it is critical to promote healthy lifestyles through health education， policy guidance， and technical resource support. For high-risk groups， emphasis should be placed on the importance of diabetes screening， coupled with combined measures of lifestyle interventions and pharmacological treatments. For diabetic patients， the focus should be on the monitoring and management of pan-risk factors associated with cardiovascular complications. China has introduced a new model for diabetes management—the National Metabolic Management Center （MMC）. By providing structured training and education for physicians within its network， the MMC promotes standardized， one-stop management solutions for diabetes， reducing regional disparities in diabetes management and effectively improving the diagnosis and treatment efficiency of diabetes and its complications. To achieve the goals of the "Healthy China 2030" initiative， concerted efforts from governments， sectors， communities， and individuals are required to raise diabetes awareness， expand standardized management coverage， and improve treatment and control rates， while reducing the incidence of diabetes and its complications. These efforts will lay a solid foundation for improving public health and building a healthy China for all.